Interpretation of sea level change using paleobiodiversity analysis: the Darende Formation of the Eocene (Malatya Basin, East Turkey) - Kaygili, Sibel; Aksoy, Ercan (Tubitak Scientific & Technological Research Council Turkey, 2019)
This study was conducted in the Paleogene-Neogene Malatya Basin situated in Eastern Anatolia with particular focus on the analyses of the paleobiodiversity of the larger benthic foraminifera assemblage found in the late Lutetian-Bartonian Yenice and Asartepe members of the Darende Formation. Frequency, dominance, similarity analyses, population size, and diversity indices of the genera/species were obtained for the first time from the analyses of the paleobiodiversity data interpretation obtained by using the larger benthic foraminifera of the Yenice and Asartepe members. According to frequency analysis values, rarely, seldom, generally, frequently, and commonly observed genera and species were determined. The frequency analysis values of the genera were between 15% and 86% for Nummulites, 9% and 81% for Assilina, and 2% and 13% for orthophragminids. Species frequency analysis values were determined for Nummulites aturicus (2%-16.98%), Nummulites beaumonti (3.77%-5.88%), Nummulites maximus (0.94%), Nummulites perforatus (19.81%-61.36%), Assilina exponens (16.98%-67.65%), Nummulites sp.1 (11.32%), and Nummulites sp.2 (30.19%). The dominance analysis values were obtained as <5, 5-25, 25-50, 50-75, and >75 for genus and species. The values of the diversity index are between 0.66 and 1.2. Similarity analysis values among sections changed between 49% and 95%. The numerical results obtained from paleobiodiversity analyses also support the fact that the distributions of the larger benthic foraminifera changed in accordance with the hydrodynamic conditions of the depositional environment. The change of frequency analysis values of orthophragminids indicates sea level changes in the environment over time. When the species were evaluated with respect to their frequency and dominance analyses, it was observed that the orthophragminids had lower values than the larger benthic foraminifera. This indicates that the depositional environments of the late Lutetian-Bartonian Yenice and Asartepe members were not deep enough to convert from shelf to slope.
Keywords: Malatya Basin; Eocene; larger benthic foraminifera; paleobiodiversity analyses